2014
DOI: 10.1007/s11426-014-5172-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of fluorination on homoleptic iridium complexes with C∧N=N type ligand to material properties, ligand orientation and OLED performances

Abstract: Two new iridium complexes with C^N=N type ligand (i.e., Ir(BFPPya) 3 {tris[3,6-bis(4-fluorophenyl)pyridazine]iridium(III)} and Ir(BDFPPya) 3 {tris[3,6-bis (2,4-di-fluorophenyl)pyridazine]iridium(III)}) attaching with fluorine atoms, were synthesized and the effects of fluorination on the material properties and device performance were investigated. Compared with our previously reported fluorine-free analogue material, that is Ir(BPPya) 3 {tris[3,6-bis(phenyl)pyridazine]iridium(III)}, blue shifts in the emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…The thermal stabilities of all complexes were analyzed by thermogravimetric analysis (TGA). It can be clearly seen that all complexes have good thermal stability above 200 °C (Figures S13 and S14), and these results are compatible with similar studies in the literature. , It is proposed that the presence of strong Ir–N bond in the structure increases the stability of complex . Furthermore, in the present study, the complexes with TFSI counterion were found to show higher thermal stability (350–435 °C) than those of complexes with PF 6 counterion as expected.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The thermal stabilities of all complexes were analyzed by thermogravimetric analysis (TGA). It can be clearly seen that all complexes have good thermal stability above 200 °C (Figures S13 and S14), and these results are compatible with similar studies in the literature. , It is proposed that the presence of strong Ir–N bond in the structure increases the stability of complex . Furthermore, in the present study, the complexes with TFSI counterion were found to show higher thermal stability (350–435 °C) than those of complexes with PF 6 counterion as expected.…”
Section: Resultssupporting
confidence: 92%
“…36,37 It is proposed that the presence of strong Ir−N bond in the structure increases the stability of complex. 38 Furthermore, in the present study, the complexes with TFSI counterion were found to show higher thermal stability (350−435 °C) than those of complexes with PF 6 counterion as expected. Previous studies have shown that the TFSI anion has higher thermal stability than the PF 6 anion.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…Pyridazine and its derivatives have received arising attention these past few years, as building blocks in organic semiconductors for OFET, solvate-chromic/fluorescent sensors, and liquid crystal materials as well as efficient ligands for strong phosphorescent iridium complexes. As a six-member heterocyclic aromatic ring, pyridazine comprises two adjacent sp 2 N. When compared with other monocyclic aromatic ring analogues of benzene without N atom and pyridine with one N atom, pyridazine is not only more electron accepting but also more polar, beneficial to its usage as electron acceptor in D–A type materials. However, for optoelectronic application, to the best of our knowledge, except for the compounds reported in ref , which were used as a semiconductor in the OFET device, pyridazine incorporated D–A bipolar materials are rare in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…PD-units, for example, have been used as ligands to coordinate with Ir, Pt, and other precious metal ions to create phosphorescent emitters for OLEDs, which emit blue light, red light, and nearinfrared (NIR) light. [70][71][72] PD-units can also be combined with -BF 2 -to construct pure organic complex-based blue fluorescent emitters, 73,74 or with arylamine groups to construct phosphorescent host materials 75,76 and thermally activated delayed fluorescence (TADF) luminescent materials. 77,78 Scheme 3 and Fig.…”
Section: Pds For Oledsmentioning
confidence: 99%